International, Transdisciplinary, and Ecohealth Action for Sustainable Agriculture in Asia - Nguyen-Viet, Hung; Pham, Giang; Lam, Steven; Pham-Duc, Phuc; Dinh-Xuan, Tung; Jing, Fang; Kittayapong, Pattamaporn; Adisasmito, Wiku; Zinsstag, Jakob; Grace, Delia (Frontiers in Public Health, 2021)
Sustainably intensifying agriculture to secure food for people, while minimizing the human, animal, and environmental health impacts is an unprecedented global food security challenge. Action research is needed to understand and mitigate impacts, with Ecosystem approaches to health (Ecohealth) emerging as a promising framework to support such efforts. Yet, few have critically examined the application of Ecohealth principles in an agriculture context, particularly in Southeast Asia where agricultural intensification is rapidly expanding. In this paper, we evaluate the strengths, challenges, and opportunities of an Ecohealth project in low-resource settings of Vietnam, Thailand, Indonesia, and China, drawing on the experiences of the Field Building Leadership Initiative. To do this, we used a developmental evaluation framework involving several iterative cycles of document analyses, interviews, focus groups, and outcome harvesting. Results highlight the importance of transdisciplinarity, participation, and knowledge-to-action principles in co-generating knowledge and solutions. However, integrating such principles were challenging concerning regional collaboration, community engagement, and resource commitment. To address such challenges, there is a need to strengthen capacity in integrated approaches, improve institutionalization of Ecohealth, foster community engagement, and continuously monitor and evaluate efforts. Ecohealth holds significant promise in advancing food security, but only when considerable time is spent developing the project with communities.